UPAYA-UPAYA PENUNDAAN KEHAMILAN DAN KELAHIRAN ANAK MASA KULIAH PADA MAHASISWA REGULER BIDANG KESEHATAN DI UNIVERSITAS DIPONEGORO - Ufthoni, Ghodiq (STIKES Widya Husada Semarang, 2010)
The research has purpose to know the correlation between efforts of pregnancy postponement and child birth of lecture period in reguler university student majoring in health at Diponegoro University. The used research desain was an explanatory reseach wich cross sectional approach. The research population was all regular university student majoring in health of Diponegoro University. Sampel taken by purposif sampling were all maried student. The used statistical test was chi square. The result of hypothesis test by using chi squre with significance 95% obtained conclusion that there is corelation between an effort of pregnancy postponement using simple method and child birth of lecture period (p value: 0,035). there is correlation between an efford of pregnancy postponement using modern contraception method and child birth of lecture periode (p value: 0,028), trere is no corelation between an efford of pregnancy postponement using traditional method and child birth of lecture period (p value: 0,155). Based on the result, is the suggested for BKKBN to pay attention to the fact that society (university student) there is an effort of pregnancy postponement using tradisional method which has not been proved it is proof scientifically, this method may not be effective or even theaten the user. Key words : method of simple family planing, method of modern contraception family planing, traditional family planing method, child birth of lecture period.